DETERMINATION OF ISONIAZID IN HUMAN URINE BY SPECTROPHOTOMETRIC METHOD - Dung, Nguyen Trung (Vietnam Journal of Science and Technology, 2015)
A simple, rapid, sensitive and accurate spectrophotometric method for the determination of isoniazid in urine has been developed. The method is based on the formation of an orange yellow colour complex between isoniazid and ammonium metavanadate in an acid medium (pH=1,80-2,20). The resulting complex  is stable for 12 hours  and has an absorption maximum at 420 nm. Beer's law is obeyed in the concentration range of 1,37-13,70 µg/ml (R2 = 0,998) with limit of detection (LOD) being 0,28 µg/ml. The molar absorptivities were  1,5.104 l.mol-1.cm-1. This method was applied to the determination of isoniazid acetylation rates (phenotypes) in healthy volunteers, patients with hepatitis B and diabetes type 2.